AGE AND ORIGIN OF THE TAKESHIKEN POSTOROGENIC ALKALI-RICH INTRUSIVE ROCKS IN SOUTHERN ALTAI, NEAR THE MONGOLIAN BORDER IN CHINA AND ITS IMPLICATIONS FOR CONTINENTAL GROWTH - Tong Y.; Wang T.; Hong D.W.; Kovach V.P.; Han B.F. (My University, 2006)
The Takeshiken alkali-rich intrusion is a typical postorogenic pluton in Chinese Altay orogen. Zircon U-Pb (TIMS) dating yield a 206Pb/238U age of 286 ± 1Ma (MSWD = 0.05), which is interpreted as its formation age. This pluton is composed of syenite with few quartz monzonite, quartz alkali-feldspar syenite and syenogranite. The rocks are enriched in K, Na, Al, REE and LILE (Rb, Th, Ba) with negative anomaly in Nb, Sr, Ti and P, different from the alkaline (A-type) granites in the same area. Their ISr values are between 0.7038 ~ 0.7040, εNd (t) values between +6.2 ~ +6.3, and TDM between 542 ~ 546 Ma, which are similar to those of high (positive) εNd (t) value granites from the Central Asian Orogenic Belt. Importantly, their εNd (t) values are higher than those of synorogenic granites, and also slightly higher than those of coeval I-A type post-orogenic granites in the central Altay. Integration analysis of field occurrence, geochronology, geochemistry and regional geology suggest that this pluton is post orogenic, and was probably related to the melting of lower crust due to the underplating of mafic magma derived from DM with enriched in LILE. This suggests that new juvenile mantle-derived materials, besides subducted juvenile ocean crust or arc rocks, probably entered into continental crust. Accordingly, this study provides evidences for vertical continental crustal growth in the Central Asian Orogenic Belt. In addition, our new data indicate that the alkali rock zone in the southern Mongolia and NE China extends to Altay orogen, constituting a large scale alkali rock zone in the Central Asia.
Keywords: ALKALI-RICH INTRUSIVE ROCK; CENTRAL ASIAN OROGENIC BELT; CRUSTAL GROWTH; ND ISOTOPE; POST-OROGENIC; ZIRCON U-PB AGE